2021
DOI: 10.1177/01455613211053389
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab-related osteonecrosis of the external auditory canal—benefit of the early surgical management

Abstract: Background: Antiresorptive drugs are widely used to reduce bone mineral loss in patients with osteoporosis and to prevent skeletal-related events in patients with metastatic cancers and multiple myeloma (MM). Both the bisphosphonates (BP) and denosumab typically used in this indication were shown to be effective and relatively safe. Obviously, this medication could have some adverse effects; one of them is osteonecrosis of the external auditory canal. Only sporadic cases of external auditory canal osteonecrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Aggressive management of side effects is vital to avoid treatment interruptions, which can be associated with rapid tumor regrowth. 1 Medication related ear canal osteonecrosis is rare, with case reports linking its development to bisphosphonates, 3 denosumab, 4 and sunitinib. 5 It can range from asymptomatic to requiring extensive surgical debridement.…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive management of side effects is vital to avoid treatment interruptions, which can be associated with rapid tumor regrowth. 1 Medication related ear canal osteonecrosis is rare, with case reports linking its development to bisphosphonates, 3 denosumab, 4 and sunitinib. 5 It can range from asymptomatic to requiring extensive surgical debridement.…”
Section: Discussionmentioning
confidence: 99%
“…In total, the author was able to identify 30 cases in the literature up until December 2022 11,15,17–33 . However, Peřina et al 2021 also reported one unpublished case of a 67– year– old female who they treated for rheumatoid arthritis with zoledronate and denosumab, who also presented with MRONJ in addition to MROEAC, but unfortunately the patient died due to cardiac comorbidity before they could publish the case 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Signs and symptoms include otalgia, otitis, otorrhea, and in advanced stages facial paresis, hearing loss and potential mastoid and TMJ involvement may occur. Early treatment may help to prevent complications 11 . In certain cases, the patient maybe asymptomatic 27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations